1993
DOI: 10.1007/bf00165384
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT1A receptor selective ligands, (R)-8-OH-DPAT and (S)-UH-301, differentially affect the activity of midbrain dopamine neurons

Abstract: The effects of the selective 5-HT1A receptor agonist (R)-8-hydroxy-2(di-n-propylamino)tetralin [(R)-8-OH-DPAT] and the novel 5-HT1A antagonist (S)-5-fluoro-8-hydroxy-2-(dipropylamino)-tetralin [(S)-UH-301] were studied with regard to the firing pattern of single mesencephalic dopamine (DA) neurons with extracellular recording techniques in chloral hydrate anesthetized male rats. Neuronal activity was studied with respect to firing rate, burst firing and regularity of firing. In the ventral tegmental area (VTA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 60 publications
5
63
0
Order By: Relevance
“…Stimulation of DA neurons was also observed with the agonists flesinoxan and S 15535 and these effects were blocked by the selective antagonist WAY 100,635 (Lejeune and Millan, 1998). The iontophoretic application of 8-OHDPAT into the midbrain excited DA neurons in VTA and SNpc in vivo (Arborelius et al, 1993a), suggesting a midbrain site of action.…”
Section: Mesolimbic Pathwaymentioning
confidence: 89%
See 1 more Smart Citation
“…Stimulation of DA neurons was also observed with the agonists flesinoxan and S 15535 and these effects were blocked by the selective antagonist WAY 100,635 (Lejeune and Millan, 1998). The iontophoretic application of 8-OHDPAT into the midbrain excited DA neurons in VTA and SNpc in vivo (Arborelius et al, 1993a), suggesting a midbrain site of action.…”
Section: Mesolimbic Pathwaymentioning
confidence: 89%
“…8-OHDPAT administration was reported to preferentially increase cortical DA relative to the dorsal striatum and NA (Arborelius et al, 1993a). While administration of 8-OHDPAT reverses D2 antagonist-induced catalepsy (Wadenberg and Ahlenius, 1991), others have provided evidence that this effect is not mediated by alterations in DA neurotransmission (Neal-Beliveau et al, 1993;Lucas et al, 1997).…”
Section: Nigrostriatal Pathwaymentioning
confidence: 99%
“…As one intriguing example, several studies in vivo have shown that stimulation of 5-HT 1A receptors can enhance the activity of VTA but not substantia nigra DA neurons, whereas application of 5-HT 1A antagonists induces the opposite effect (38, 39, 44). For example 8-OH-DPAT, a 5-HT 1A receptor agonist, increased the firing rate, regularity of firing, and burst firing of VTA DA neurons in rats (38,39). In contrast, the same drug did not alter any of the firing patterns of DA neurons in the substantia nigra (38).…”
Section: Discussionmentioning
confidence: 99%
“…For example 8-OH-DPAT, a 5-HT 1A receptor agonist, increased the firing rate, regularity of firing, and burst firing of VTA DA neurons in rats (38,39). In contrast, the same drug did not alter any of the firing patterns of DA neurons in the substantia nigra (38). This result raises the possibility that serotonergic afferents into the midbrain may mediate, in part, the DA-elevating actions of AMPH in the NAc of DAT-KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation